The Gambia Government Social Networking Coordination-Preparedness and Response to COVID-19 - Mbassi Sanneh; Khairul Munadi; Alfi Rahman (Proceedings of AICS - Social Sciences, 2020)
The 95th National Situation Report revealed that The Gambia has 61 confirmed cases, 27 recoveries, and 3 died as of July 5, 2020. Cases are mostly imported with few local transfers. COVID-19 has now gone beyond health crisis which required a holistic coordination approach to curb the virus lessons learned from countries. The fight is an all-inclusive networking approach to curb the spread. The research objective is to map out government social networking and teamwork preparedness and responding to COVID-19. The methodology of the research is a qualitative approach through online literature reviewing newspapers, reports, and articles. The secondary source of data was also harvested from the Gambia National COVID-19 Response Plan 2020. This mapping aims to identify and know partnership collaboration and interaction as a team working towards the objectives and goal for preparedness and response to prevent repetition of efforts. Social Networking Analysis (SNA) becomes a tool for social network limelight showing the connection for coordination, interaction, communication on common interests, shared values, financial exchanges, and standard operating procedures against the implementation of COVID-19 programs. There will be the maximisation of duplication of resources and efforts and informed decisions on who is doing what, where, when, and how.